Challenges in the Surgical Management of Large Osteoma in the Maxillary Sinus: Case Report - Melo, Radamés Bezerra; Azevedo, Sara Rodrigues; Freitas, Luiz Henrique Ferreira; Pinheiro Moraes, Raissa; Gusmão, Jonas Nogueira Ferreira Maciel (Brazilian Journal of Case Reports, 2024)
Osteoma is a benign neoplasm characterized by slow growth and can be composed of spongy or compact bone. Its symptomatology is directly related to the location, size, and proximity to adjacent structures. Histologically, it is classified as compact, cancellous, or mixed. Although rarely found in the gnathic bones, they are more frequently observed in the paranasal sinuses. This study aims to report a case of osteoma located in the maxillary sinus of a male patient, describing the surgical management performed in a hospital setting. The patient, a 49-year-old male with no systemic diseases, underwent surgical procedure under general anesthesia, including intraoral access, excision of the lesion, and subsequent fixation of the bone fragment. After six months of postoperative follow-up, no recurrences were observed. It is concluded that the definitive treatment of osteoma requires adequate correlation of the clinical picture, selection of the best type of surgical access, consideration of the location, and choice of the most appropriate synthesis method to promote a good prognosis.